Evaluation of systemic activity of pediatric primary Sjögren's syndrome by EULAR Sjögren's syndrome disease activity index (ESSDAI). Issue 1 (2nd January 2019) - Kobayashi, Ichiro; Okura, Yuka; Ueki, Masahiro; Tozawa, Yusuke; Takezaki, Shunichiro; Yamada, Masafumi; Ariga, Tadashi
Abstract: Objectives: The purpose of this study is to evaluate systemic disease activity of pediatric Sjögren's syndrome (SS) using European League Against Rheumatism (EULAR) Sjögren's syndrome disease activity index (ESSDAI). Methods: We retrospectively reviewed medical records of patients with SS who have been diagnosed according to 1999 Japanese diagnostic criteria for SS before 16 years old at KKR Sapporo Medical Center, Hokkaido University Hospital, and affiliated hospitals. We analyzed clinical and laboratory data and calculated ESSDAI at both diagnosis and peak activity. Results: Twenty-five patients (2 boys and 23 girls) were enrolled. Only 4 patients had sicca symptoms at diagnosis. Mean ESSDAI scores at diagnosis and peak activity were 12.68 (2–31) and 15.08 (2–38), respectively. Only 3 patients were inactive (ESSDAI score <5) at diagnosis. Frequently involved domains at diagnosis were the biological (96%) followed by the constitutional (68%), glandular (44%), articular (44%), cutaneous domains (28%), renal (16%), and central nervous system (12%). At peak activity, biological domain (96%) was followed by the constitutional (72%), glandular (60%), articular (44%), cutaneous (28%), central nervous system (20%), and renal domains (16%). Conclusion: Pediatric SS is suspected from active systemic manifestations. The items of ESSDAI are useful clues to the diagnosis of pediatric SS.